Pengaruh Budaya Lokal Katimaha terhadap Pembentukan Spiritualitas dalam Persefektif Psikologi Keagamaan - As sudays, Adzani Ashari Dayang; Jaenal, Muhammad; Saleh, Muhammad Nabil Bani; Selvi, Selvi; Nasyifa, Yahdelina; Batubara, Noor Azida (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2026)
Globalization and modernization threaten the erosion of local wisdom values in Indonesia, including Katimaha culture in Katimaha Village, Bekasi, emphasizing tepo seliro, musyawarah, and gotong royong as foundations of moderate spirituality. This study aims to identify the role of Katimaha culture in forming moderate spirituality from religious psychology perspective. Employing qualitative phenomenological approach, population comprised active residents of Katimaha Village with purposive sample of religious leaders, traditional figures, and youth. Main instrument was researcher supported by triangulation of participatory observation, in-depth interviews, and documentation; data analysis through Miles-Huberman's reduction, thematic display, and verification. Findings reveal Katimaha culture functions as socio-psychological mechanism for internalizing moderate values through pengajian, mutual cooperation, and deliberation, producing hablum minallah wa hablum minannas balance. Conclusion states Katimaha preservation proves effective as local wisdom-based character education strategy for religious moderation.